Przyczyny i polityczne skutki wyborów uzupełniających do Senatu RP - Leszczyńska, Krystyna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
Wybory uzupełniające do Senatu RP w ocenie polskich polityków spełniają funkcję barometru odzwierciedlającego nastroje polityczne społeczeństwa. Celem artykułu jest wskazanie przyczyn i politycznych skutków wygasania mandatu senatora w trakcie kadencji. Porównując wyniki badań, uzyskane w rezultacie analizy zagadnienia określonego w tytule artykułu, podjęto próbę odpowiedzi na następujące pytania badawcze: 1) jakie czynniki wpływają na wygaśnięcie mandatu senatora w Polsce?; 2) jak kształtuje się frekwencja w tych wyborach na tle frekwencji w wyborach do Sejmu i Senatu?; 3) w jakim stopniu wybory uzupełniające do Senatu wpływają na zmianę jego kompozycji politycznej?; 4) czy stanowią one wiarygodny barometr nastrojów politycznych społeczeństwa? Zastosowane metody badawcze (instytucjonalno-prawna, statystyczna, porównawcza) pozwoliły sformułować wnioski. Dotychczas wygasło 44 mandaty senatorskie (4,9%). Głównymi przyczynami były: śmierć (36,4%), objęcie ważnych stanowisk publicznych (22,8%) i wybór na posła do PE (15,9%). Przeprowadzone 37 razy elekcje uzupełniające do Senatu z reguły wywoływały niewielkie zainteresowanie wyborców (najczęściej około 7%). Jednak zdarzało się, że ich wyniki sygnalizowały nadchodzącą zmianę polityczną (elekcje uzupełniające w IV, V i VIII kadencji) lub kontynuację istniejącego układu politycznego (elekcje uzupełniające w VI kadencji). Skuteczność tego prognostyka jest dość zawodna; okazała się trafna w czterech z siedmiu kadencji Senatu.

In the opinion of Polish politicians, by-elections to the Senate of the Republic of Poland have a barometer function, reflecting the political climate in the society. The objective of the present article is to indicate the reasons for and political consequences of mid-term expiry of senators’ mandates. In comparing the research results obtained by analyzing the topic of this article we attempted to answer the following research questions: 1) what factors influence the expiry of senators’ mandates in Poland?; 2) what is voter turnout in these elections, when compared to the ordinary elections to the Polish parliament (Sejm and Senate)? 3) to what extent do the by-elections to the Senate influence the change in its political composition?; 4) do they form a credible barometer of the political climate in the society? The research methods applied (institutional-legal, statistical, and comparative) allowed us to formulate our conclusion. So far, 44 senators’ mandates (4.9%) have expired. The main reasons for that have been death (36.4%), appointment to high public offices (22.8%), or being elected EMP (15.9%). The Senate by-elections have been conducted 37 times, and they have usually generated limited interest of voters (usually around 7%). Nevertheless, in several cases their results signalled the upcoming political change (by-elections in the IV, V and VIII terms) or the continuation of the existing political arrangement (by-elections in the VI term of office). The general efficiency of this forecast is rather elusive; it turned out to be correct in four out of seven terms of Senate.
Reasons and political consequences of by-elections to the Polish Senate
Keywords: Senat RP; wybory uzupełniające; wygaśnięcie mandatu; prognoza polityczna; Senate of the Republic of Poland; by-elections; expiry of mandate; political forecast